Metal electrode system for electrochemical cells
By adding redox mediators, such as DHPS, to the anode electrolyte of zinc-based flow cells, redox-mediated "dead zinc" regeneration is achieved, and dendrite formation and irreversible capacity loss in zinc-based flow cells are solved. Problem, improving battery stability and cycling performance.
Patent Information
- Application Number
- CN202380041881.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2023-03-24
- Publication Date
- 2025-01-10
AI Technical Summary
The zinc-based liquid flow battery forms dendrites due to uneven reactions during repeated plating/peeling, resulting in the accumulation of "dead zinc" and irreversible capacity loss, limiting the stability and cycle life of the battery.
Introduce redox mediators such as 7,8-dihydroxy-2-phenylazine sulfonic acid (DHPS) or sulfonated ferrocene into the anode electrolyte, and the "dead zinc" is oxidized through a redox-mediated process and Regenerate on the electrode to avoid irreversible capacity loss.
Effectively reverses the accumulation of "dead zinc", improves the cycle stability and capacity utilization of zinc-based flow batteries, extends the service life of the battery, and maintains a high discharge capacity under high current density and deep discharge conditions. .
Smart Images

Figure CN119301781A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a redox flow battery, to an electrolyte suitable for use in a redox flow battery, and to a kit comprising a catholyte and an anolyte, the kit being suitable for use in a redox flow battery. Background Art
[0002] The listing or discussion of a previously published document in this specification should not be taken as an admission that the document is part of the prior art or is common general knowledge.
[0003] Energy utilization is vital to human beings and gives vitality to the development of society. However, the energy structure dominated by fossil fuels has encountered major issues of sustainable development. Therefore, the development of green and renewable energy such as wind and solar energy has been widely implemented worldwide as a consensus. However, these renewable energy sources are usually intermittent and unpredictable, and the resulting power fluctuations have an impact on the safe and stable operation of the power grid, leading to unexpected power outages. In response, electrochemical energy storage (EES) technology has emerged as an important means to solve this problem. Among the many EES technologies, aqueous redox flow batteries (ARFBs) are considered to be one of the most promising large-scale energy storage technologies due to their significant characteristics of high safety, decoupling of energy storage and power generation, and good scalability. Vanadium flow battery (VFB) is one of the mature ARFB systems and has shown great advantages in operation since it was first reported in 1985. However, the deployment of VFBs faces challenges such as high cost, low energy density, corrosive electrolytes, and mediocre thermal stability, which limit their widespread application.
[0004] Zinc-based flow batteries have attracted considerable attention due to their low material cost, high cell voltage, earth abundance, and low toxicity. However, with repeated stripping / plating reactions of the zinc anode, zinc dendrites are often formed due to non-uniform reactions. At higher current densities and areal capacities, the growth of dendrites becomes more severe, and some dendrites may fall off the electrode and become "dead zinc", resulting in irreversible capacity loss, especially under deep discharge conditions. In order to eliminate "dead zinc" and capacity loss, most studies have focused on preventing the formation of dendrites through uniform zinc plating / stripping processes, such as by introducing additives in the electrolyte, optimizing electrode structure, and designing advanced membranes. Although these strategies have shown good improvements in battery stability and cycle life, the accumulation of "dead zinc" and irreversible capacity loss still exist. As a result, batteries usually operate with limited capacity and at relatively low depth of discharge (DOD) / charge.
[0005] Therefore, new zinc-based flow batteries are needed to overcome at least one of the above problems. Summary of the invention
[0006] The present inventors have surprisingly found that including a redox mediator in the anolyte can reverse the accumulation of "dead zinc" and avoid irreversible capacity loss in redox flow batteries. Accordingly, the present invention provides the following.
[0007] 1. A redox flow battery comprising:
[0008] a catholyte chamber comprising a catholyte and a cathode;
[0009] an anolyte chamber comprising an anolyte and an anode, the anode comprising a first metal; and
[0010] an ion selective membrane arranged between the cathode chamber and the anode chamber,
[0011] in:
[0012] a first metal selected from the group consisting of alkali metals, alkaline earth metals, Group III metals, and transition metals;
[0013] The anolyte comprises an anodic redox mediator; and
[0014] The anodic redox mediator has a redox potential relative to a standard hydrogen electrode that is more positive than the redox potential of the first metal relative to a standard hydrogen electrode.
[0015] 2. The redox flow battery according to clause 1, wherein the anode redox mediator is selected from one or more of the group consisting of phenazine redox mediators, quinone redox mediators, viologen redox mediators, ferrocene derivatives, nitrogen oxide radical redox mediators, and alloxazine redox mediators;
[0016] Optionally, the anodic redox mediator is selected from one or more of the group consisting of 7,8-dihydroxy-2-phenazine sulfonic acid (DHPS), amino acid functionalized phenazine, dihydroxyanthraquinone or its derivatives, sulfonated ferrocene and alloxazine 7 / 8-carboxylic acid,
[0017] More optionally, the anodic redox mediator is selected from one or more of the group consisting of DHPS and sulfonated ferrocene.
[0018] 3. The redox flow battery of clause 1, wherein the cathode electrolyte further comprises a cathode redox mediator.
[0019] 4. A redox flow battery according to clause 3, wherein the cathode redox mediator comprises one or more of the following pairs:
[0020] [Fe(CN)6] 3- / [Fe(CN6)] 4- ;
[0021] O2 / OH - ;
[0022] MnO4 - / MnO4 2- ;
[0023] I3 - / I - ;
[0024] Br2 / Br - ;
[0025] (I - Br - / I3 - ,I2Br - );
[0026] Fe 3+ / Fe 2+ ;
[0027] (2,2,6,6-tetramethylpiperidin-1-yl)oxy (TEMPO) derivatives; and
[0028] MnO2 / Mn 2+ .
[0029] 5. A redox flow battery according to clause 3 or clause 4, wherein the concentration of the cathode redox mediator in the cathode electrolyte is at least 0.3M, such as at least 0.5M, such as at least 1M.
[0030] 6. A redox flow battery according to any of the preceding clauses, wherein the cathode electrolyte comprises a salt of a first metal,
[0031] Optionally, the salt of the first metal is an oxide of the first metal or a hydroxide of the first metal.
[0032] 7. A redox flow battery according to any of the preceding clauses, wherein the concentration of the anodic redox mediator in the anolyte is from 0.001 M to 1 M,
[0033] Optionally, 0.01M to 0.05M,
[0034] More optionally, 0.015M to 0.035M,
[0035] Such as 0.02M to 0.03M.
[0036] 8. A redox flow battery according to any of the preceding clauses, wherein:
[0037] (a) the catholyte and the anolyte each comprise an inorganic base; or
[0038] (b) The catholyte and the anolyte each contain a neutral metal salt.
[0039] 9. A redox flow battery according to clause 8 or 9, wherein:
[0040] (a) the catholyte and the anolyte each comprise an inorganic base, and the anodic redox mediator is DHPS; or
[0041] (b) The catholyte and anolyte each comprise a neutral metal salt, and the anodic redox mediator is sulfonated ferrocene.
[0042] 10. A redox flow battery according to clause 8 or 9, wherein:
[0043] (a) the inorganic base is selected from one or more of NaOH, LiOH and KOH;
[0044] (b) A neutral metal salt is one or more selected from the group consisting of MCl, MBr, M2SO4, and MNO3, wherein M is selected from Li, Na, K, and NH4.
[0045] 11. A redox flow battery according to any of the preceding clauses, wherein the first metal is selected from the group consisting of alkali metals, alkaline earth metals, aluminum, zinc and iron;
[0046] Optionally, wherein the first metal is selected from the group consisting of lithium, potassium, sodium, magnesium, aluminum, zinc and iron.
[0047] 12. A redox flow battery according to any of the preceding clauses, wherein the first metal is Zn.
[0048] 13. The redox flow battery according to clause 12, wherein the areal capacity of zinc in the redox flow battery is 10 mAh / cm 2 Up to 450mAh / cm 2 , such as 10mAh / cm 2 Up to 300mAh / cm 2 , such as 12mAh / cm 2 Up to 250mAh / cm 2 , such as 12.2mAh / cm 2 Up to 250mAh / cm 2 .
[0049] 14. A redox flow battery according to any of the preceding clauses, wherein the anode comprises carbon and a first metal,
[0050] Optionally, wherein the anode comprises carbon fibers and a first metal.
[0051] 15. A redox flow battery according to any one of the preceding clauses, wherein the current density of the redox flow battery is 10 mA / cm 2 Up to 300mA / cm 2 , such as 10mA / cm 2 Up to 200mA / cm 2 , such as 10mA / cm 2 Up to 100mA / cm 2 , such as 20mA / cm 2 Up to 80mA / cm 2 .
[0052] 16. A redox flow battery according to any one of the preceding clauses, wherein the discharge capacity of the redox flow battery is 10 mAh / cm 2 Up to 450mAh / cm 2 , such as 10mAh / cm 2 Up to 300mAh / cm 2 , such as 12mAh / cm 2 Up to 250mAh / cm 2 , such as 12.2mAh / cm 2 Up to 250mAh / cm 2 .
[0053] 17. A redox flow battery according to any preceding clause, wherein the capacity fade rate of the redox flow battery is less than 0.02% / day for at least 1500 hours.
[0054] 18. A redox flow battery according to any of the preceding clauses, wherein the catholyte and anolyte are aqueous.
[0055] 19. A redox flow battery according to any preceding clause, wherein:
[0056] The anodic redox mediator comprises DHPS;
[0057] The catholyte contains [Fe(CN)6] 3- and [Fe(CN6)] 4- One or both of the following:
[0058] The first metal comprises Zn;
[0059] The catholyte and anolyte each comprise an inorganic base (e.g., NaOH); and
[0060] The catholyte contains zinc oxide or zinc hydroxide.
[0061] 20. A redox flow battery according to any one of clauses 1 to 18, wherein:
[0062] The anodic redox mediator comprises sulfonated ferrocene;
[0063] The catholyte contains I - and I2Br - One or both of the following:
[0064] The first metal comprises Zn;
[0065] The catholyte and anolyte each comprise a neutral metal salt (e.g., NaCl, KBr, and / or KCl); and
[0066] The catholyte comprises a neutral zinc salt (eg, ZnCl2, ZnBr2 and / or ZnI2).
[0067] 21. A redox flow battery according to clause 19 or 20, wherein the catholyte and anolyte are aqueous.
[0068] 22. An electrolyte suitable for use in a redox flow battery, comprising:
[0069] Solvent (e.g. water);
[0070] Neutral or basic metal salts; and
[0071] One or more redox mediators selected from the group consisting of DHPS and sulfonated ferrocene.
[0072] 23. An electrolyte according to clause 22, wherein:
[0073] The metal salt comprises zinc oxide or zinc hydroxide; and
[0074] The redox mediator is DHPS.
[0075] 24. The electrolyte according to item 22 or 23, further comprising an inorganic base,
[0076] Optionally, wherein the inorganic base comprises NaOH.
[0077] 25. A kit comprising:
[0078] (i) a catholyte comprising:
[0079] an oxide of a first metal or a hydroxide of a first metal, and
[0080] Neutral or basic metal salts; and
[0081] (ii) an anolyte comprising:
[0082] a redox mediator having a redox potential relative to a standard hydrogen electrode that is more positive than the redox potential of the first metal relative to a standard hydrogen electrode, and
[0083] Neutral or basic metal salts.
[0084] 26. A kit according to clause 25, wherein:
[0085] The first metal is zinc;
[0086] The neutral or alkaline metal salt is selected from NaCl and NaOH;
[0087] The redox mediator is one or more selected from the group consisting of DHPS and sulfonated ferrocene,
[0088] Provided that when the metal salt is NaCl, the redox mediator is sulfonated ferrocene, and when the metal salt is NaOH, the redox mediator is DHPS. BRIEF DESCRIPTION OF THE DRAWINGS
[0089] Figure 1 Depicted is a conceptual illustration of the regeneration of "dead zinc" from the anode through a redox-mediated reactivation process. Upon repeated plating / stripping, "dead zinc" falls off the carbon felt matrix and loses electrical contact with the electrode. During the discharge process, after the "active zinc" on the electrode is depleted, the soluble redox mediator (RM) dissolved in the electrolyte further oxidizes the "dead zinc" and transfers electrons to the electrode through a redox-targeted process.
[0090] Figure 2 Depicted is 50 mM [Zn(OH)4] 2- CV curves of 5 mM DHPS / 3.8 M NaOH and 5 mM DHPS / 3.8 M NaOH. Working electrode: glassy carbon disk; Scan rate: 0.05 V / s.
[0091] Figure 3 The CV curves of 5 mM Fc-SO3Na / 1 M NaCl and 0.1 M ZnCl2 / 1 M NaCl solutions on a glassy carbon electrode are depicted at a scan rate of 0.05 V / s.
[0092] Figure 4 Plotted at 30 mA / cm 2 DHPS / [Fe(CN)6] 3- / 4- Four-electrode measurement of various potential differences in a flow battery. As shown in the figure, the ΔV between the charge and discharge processes + and ΔV - It is almost negligible, and the main resistance comes from the membrane and other series resistances of the device.
[0093] Figure 5 Depicted (a) at 20 mA / cm 2 The areal capacity with and without 20 mM DHPS in the anolyte was 12.2 mAh / cm 2 Cycling performance of two Zn-based symmetric flow batteries. (b) Representative voltage profiles of the cell with DHPS in the anolyte in (a). (c) Cycling performance of two Zn-based symmetric flow batteries with DHPS in the anolyte in (a). (d) Representative voltage profiles of the cell with DHPS in the anolyte in (a). (e) 2 The areal capacity of 20 mM DHPS in the anolyte is 92 mAh / cm 2 Cycling performance of the zinc-based symmetric flow battery. (d) Voltage distribution of the battery at the 5th, 40th, and 80th cycles in (c).
[0094] Figure 6 Depicted are (a) the areal capacity of zinc with and without DHPS in the anolyte is 12.2 mAh / cm 2 (a) Cycling performance of two zinc-based symmetric cells from 120 to 175 cycles. The cathode electrolyte system was replaced at the 140th cycle. (b) Voltage profiles of the cell with DHPS at the 5th and 145th cycles. The current density was 20 mA / cm 2 .
[0095] Figure 7 Depicted at 12.2 mAh / cm 2 At 20mA / cm 2 Scanning electron microscope (SEM) images of (a) the pristine carbon felt electrode, (b) the electrode without DHPS, and (c) the electrode with DHPS after 175 cycles (discharged state).
[0096] Figure 8 Pristine carbon felt electrode and the electrodes without and with DHPS in the anolyte at 20 mA / cm 2 X-ray diffraction (XRD) pattern of the electrode after 175 cycles (discharge state) under test. The areal capacity of zinc in the battery is 12.2 mAh / cm 2 .
[0097] Fig. 9 Depicted is the DHPS-mediated zinc symmetric flow battery at 50 mA / cm 2 The cumulative discharge capacity of the battery after 78 cycles (3rd to 80th cycles) of continuous testing (about 11.9 days) at a current density of 1.38 W. The theoretical capacity is based on the area discharge capacity in the 3rd cycle (0.0912 Ah / cm 2 ) because the first two cycles have a capacity increase (see Fig.11 c), which is presumably the result of the activation of the ZnO passivation layer on the zinc plate.
[0098] Fig.10 Depicted at 92 mAh / cm 2 At 50mA / cm 2 SEM image of the carbon felt electrode with DHPS in the anolyte after 80 cycles (discharged state).
[0099] Fig.11 Depicted at 92 mAh / cm 2 At 50mA / cm 2 XRD pattern of the carbon felt electrode with DHPS in the anolyte after 80 cycles (discharged state).
[0100] Fig.12 The galvanostatic cycling performance of a zinc-based symmetric flow battery with Fc-SO3Na in the anolyte under neutral conditions is depicted: the catholyte is 1 M ZnCl2 (80 mL) and the anolyte is 20 mM Fc-SO3Na / 1 M ZnCl2 (20 mL). The current density is 20 mA / cm 2 The zinc used for the anode and cathode were 0.2 g and 2 g, respectively.
[0101] Fig.13 A summary of RMs for redox-mediated zinc anodes for redox flow battery applications is depicted.
[0102] Fig.14 Depicted (a) at 50 mA / cm 2 The area capacity of Zn is 152 mAh / cm 2 The cycling performance of an alkaline zinc-iron flow battery (AZIFB) with 30 mM DHPS in the anolyte was investigated. 110 mL and 300 mL of 3.8 M OH were added, respectively. - with 30 mM DHPS and 0.6 M Fe(CN)6 3- / 0.05M Fe(CN)6 4- / 1.8M OH - 2.5 g of zinc was used as the anolyte and catholyte. (b) Cumulative areal discharge capacity of the above AZIFB after 247 cycles of continuous testing over 2 months. (c) Constant current voltage distribution of the above AZIFB in the 10th, 150th and 200th cycles. The current density is 50 mA / cm 2 .
[0103] Fig.15 Depicted is a zinc loading of 92 mAh / cm in the absence of DHPS in the anolyte 2The cycling performance of AZIFB under the condition of current density of 20mA / cm 2 .
[0104] Fig.16 Depicted (a) at 152 mAh / cm 2 At 50mA / cm 2 SEM image of the carbon felt electrode from the redox-mediated AZIFB after 248 cycles (discharged state). (b) Energy dispersive spectroscopy (EDS) plot of the C element. (c) Energy dispersive X-ray (EDX) spectrum of the carbon felt. No zinc was detected from the EDX measurement.
[0105] Fig.17 Depicted at 152 mAh / cm 2 , at 50mA / cm 2 XRD pattern of the carbon felt electrode from redox-mediated AZIFB after 248 cycles (discharged state).
[0106] Fig.18 Plotted at 50 mA / cm 2 Under the condition of charging, the area capacity is 152mAh / cm 2 SEM images of the surface of the carbon felt electrode. (a,c) without DHPS in the anolyte and (b,d) with DHPS in the anolyte.
[0107] Fig.19 Plotted at 50 mA / cm 2 Under the condition of charging, the area capacity is 152mAh / cm 2 SEM images of cross sections of carbon felt electrodes (a, c) without DHPS in the anolyte and (b, d) with DHPS in the anolyte.
[0108] Fig. 20 Plotted at 80 mA / cm 2 The area capacity of zinc is 200 mAh / cm 2 And the cycling performance of AZIFB with 30 mM DHPS in the anolyte was also improved.
[0109] Fig.21 Plotted at 80 mA / cm 2 The area capacity of zinc is 250 mAh / cm 2 And the cycling performance of AZIFB with 30 mM DHPS in the anolyte was also improved.
[0110] Fig. 22Depicted is a solubility test of ZnO in 3.8M NaOH. The test was performed by dissolving ZnO in 15mL of 3.8M NaOH solution until saturation was reached. The solubility was about 0.5M. DETAILED DESCRIPTION
[0111] In the embodiments herein, the word "includes" can be interpreted as requiring the features mentioned, but not limiting the presence of other features. Alternatively, the word "includes" can also refer to situations where only the listed components / features are intended to exist (e.g., the word "includes" can be replaced by the phrase "consisting of..." or "consisting essentially of..."). It is explicitly considered that both the broader interpretation and the narrower interpretation can be applied to all aspects and embodiments of the present invention. In other words, the word "includes" and its synonyms can be replaced by the phrase "consisting of..." or the phrase "consisting essentially of..." or its synonyms, and vice versa.
[0112] The present invention provides a redox flow battery, comprising:
[0113] a catholyte chamber comprising a catholyte and a cathode;
[0114] an anolyte chamber comprising an anolyte and an anode, the anode comprising a first metal; and
[0115] an ion selective membrane arranged between the cathode chamber and the anode chamber,
[0116] in:
[0117] a first metal selected from the group consisting of alkali metals, alkaline earth metals, Group III metals, and transition metals;
[0118] The anolyte comprises an anodic redox mediator; and
[0119] The anodic redox mediator has a redox potential relative to a standard hydrogen electrode that is more positive than the redox potential of the first metal relative to a standard hydrogen electrode.
[0120] The ion selective membrane separates the cathode chamber from the anode chamber. It can be an electroactive charge balance ion conducting membrane (e.g., potassium, lithium or sodium ion conducting membrane). The ion selective membrane prevents cross diffusion of redox mediators and allows the movement of electroactive charge balance ions (e.g., potassium, lithium ions, sodium ions, magnesium ions, aluminum ions, copper ions, protons or combinations thereof). For example, the separator can be Nafion TM Membrane, lithium phosphorus oxynitride glass, lithium thiophosphate glass, sodium phosphorus oxynitride glass, sodium thiophosphate glass, NASICON type lithium conductive glass ceramics, NASICON type sodium conductive glass ceramics, garnet type lithium or sodium conductive glass ceramics, ceramic nanofiltration membrane, lithium or sodium ion exchange membrane or a suitable combination thereof.
[0121] Both the cathode chamber and the anode chamber comprise electrodes (i.e., cathode and anode), which may comprise carbon, metal, or a combination thereof, provided that the anode comprises a first metal (which may be present in addition to carbon). Preferably, the two electrodes have a high surface area, with or without one or more catalysts, to facilitate the charge collection process. They may be made of carbon, metal, or a combination thereof. Examples of electrodes may be found in Skyllas-Kazacos et al., Journal of The Electrochemical Society, 158, R55-79 (2011) and Weber et al., Journal of Applied Electrochemistry, 41, 1137-64 (2011).
[0122] In some embodiments of the invention that may be mentioned herein, the anode may comprise carbon and a first metal. For example, the anode may comprise carbon fibers and a first metal.
[0123] The catholyte and anolyte each comprise a supporting electrolyte, which may comprise a solvent and one or more ion-donating compounds or salts, as discussed further herein.
[0124] A suitable solvent for supporting the electrolyte is water, which can be used alone or in combination with an organic solvent suitable for use in a battery. The organic solvent can be used as an additive to adjust the standard potential of the active material. Suitable organic solvents that may be mentioned herein include, but are not limited to, alcohols, carbonates, ethers, esters, ketones and nitriles.
[0125] Suitable alcohols that may be mentioned herein include, but are not limited to, methanol, ethanol, n-propanol, and isopropanol, etc. Suitable carbonates include cyclic carbonates (such as propylene carbonate, ethylene carbonate, diethyl carbonate, butylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, and / or vinylene carbonate, etc.) and linear carbonates (such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, etc.). Suitable ethers include glycol dimethyl ether solvents and cyclic or linear ethers other than glycol dimethyl ether (such as tetrahydrofuran (and its derivatives), 1,3-dioxane, 1,4-dioxane, 1,2-dimethoxyethane, and 1,4-dibutoxyethane, etc.). Suitable esters include linear esters (such as methyl formate, methyl acetate, and methyl butyrate, etc.). Suitable nitriles include, but are not limited to, acetonitrile and benzonitrile, etc. Other solvents that may be mentioned include dioxolane or its derivatives, ethylene sulfide, cyclopentane, and sultone or its derivatives.
[0126] Suitable glyme solvents may be selected from one or more of the group consisting of ethylene glycol dimethyl ether (monoglyme), diglyme, triglyme, tetraglyme, methyl nonafluorobutyl ether (MFE) and analogs thereof. Analogs of tetraglyme (CH3(O(CH2)2)4OCH3) that may be mentioned include, but are not limited to, compounds in which one or both CH3 end groups may be modified to -C2H5 or to -CH2CH2Cl or other similar substituents. In certain embodiments of the present invention that may be mentioned herein, the glyme solvent is tetraglyme.
[0127] As will be appreciated, water can be used in the systems described herein as part of the supporting electrolyte. In other words, the catholyte and anolyte can be aqueous. When water is used, it can be the only solvent, or an organic solvent can be used as an additional solvent in any suitable weight ratio relative to water. For example, the additional solvent can be selected from one or more of the group of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, tetrahydrofuran, cyclopentane, acetonitrile and tetraglyme.
[0128] Alternatively, the system described herein can be non-aqueous. That is, the anolyte and catholyte can contain only an organic solvent and no water. In this case, the organic solvent can be selected from one or more of the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, tetrahydrofuran, cyclopentane, acetonitrile and tetraglyme.
[0129] In specific embodiments that may be mentioned herein, the solvent for the catholyte and anolyte may be water alone or in combination with a glyme solvent (eg, water and tetraglyme).
[0130] As described above, the anolyte contains an anodic redox mediator. As used herein, the term "redox mediator" refers to a compound present (eg, dissolved) in the catholyte or anolyte that acts as a molecular shuttle to transport electrons during charge / discharge of the battery.
[0131] The anodic redox mediator has a redox potential relative to the standard hydrogen electrode that is more positive than the redox potential of the first metal relative to the standard hydrogen electrode. In other words, the anodic redox mediator is capable of oxidizing the first metal so that any portion of the deposited first metal separated from the anode, i.e., "dead metal", can be oxidized by the anodic redox mediator and put back into solution. As will be appreciated by those skilled in the art, the nature of the anodic redox mediator is not particularly important, provided that it is capable of oxidizing the first metal under the conditions (e.g., pH) of the anolyte. Fig.13Examples of possible redox mediators are provided in FIG, and one skilled in the art will be able to readily identify from this figure which redox mediators will be suitable for use with any particular metal.
[0132] In some embodiments of the present invention that may be mentioned herein, the anodic redox mediator may be selected from one or more of the group consisting of phenazine redox mediators, quinone redox mediators, viologen redox mediators, ferrocene derivatives, nitrogen oxide free radical redox mediators and alloxazine redox mediators. For example, the anodic redox mediator may be selected from one or more of the group consisting of DHPS, amino acid functionalized phenazine, dihydroxyanthraquinone or its derivatives, sulfonated ferrocene and alloxazine 7 / 8-carboxylic acid, such as one or more of the group consisting of DHPS and sulfonated ferrocene.
[0133] A specific example of sulfonated ferrocene that may be mentioned here is ferrocenesulfonate, sodium salt.
[0134] The catholyte may contain a cathodic redox mediator. Examples of suitable cathodic redox mediators include one or more of the following pairs: [Fe(CN)6] 3- / [Fe(CN6)] 4- ; O2 / OH - ; MnO4 - / MnO4 2- ;I3 - / I - Br2 / Br - ;(I - ,Br - / I3 - , I2Br - );Fe 3+ / Fe 2+ ; (2,2,6,6-tetramethylpiperidin-1-yl)oxy (TEMPO) derivatives; and MnO2 / Mn 2+ .
[0135] Specific examples of cathode redox mediators include [Fe(CN)6] 3- / [Fe(CN6)] 4- and / or Br - / Br2.
[0136] In the redox mediator containing [Fe(CN)6] 3- / [Fe(CN6)] 4- In the embodiment, [Fe(CN)6] 3- The redox mediator can be ferrocyanide (M3Fe(CN)6), and [Fe(CN6)] 4-The redox mediator may be ferrocyanide (M4Fe(CN)6), wherein in each case, M is independently selected from the group consisting of Li, Na, K and NH4, optionally wherein M is K.
[0137] In the redox mediator containing Br - / Br2 embodiment, Br - The redox mediator may be MBr, wherein in each case, M is independently selected from the group consisting of Li, Na, K and NH 4 , optionally wherein M is K.
[0138] In certain embodiments described herein, the supporting electrolyte may further comprise a redox mediator other than the above-mentioned anode / cathode redox mediator. The additional redox mediator may be selected from Zn / Zn 2+ Redox mediator, Fe 2+ / 3+ , transition metal complexes, metallocenes, triarylamines, phenothiazine derivatives, phenoxazine derivatives, carbazole derivatives, aromatic derivatives, nitrogen oxide free radicals, disulfides, polysulfides, viologen, quinone derivatives, ferrocene (C 10 H 10 Fe) and its derivatives, iodide (MI) and bromide (MBr), wherein in each case, M is independently selected from the group consisting of Li, Na, K and NH4. In more specific embodiments that may be mentioned herein, the additional redox mediator may be selected from the group consisting of Zn / Zn 2+ Redox mediator, Fe 2+ / 3+ , ferrous ion of o-phenanthroline, iron (II / III) tris (2,2'-bipyridine), iron (II / III) tris (2,2'-methylbipyridine), iron (II / III) tris (2,2'-methoxybipyridine), viologen, quinone derivatives, ferrocene (C 10 H 10 One or more of the group consisting of Fe) and its derivatives, iodide (MI) and bromide (MBr), wherein in each case, M is independently selected from the group consisting of Li, Na, K and NH4.
[0139] Examples of various redox mediators that may be used in the present invention (whether as the anode, cathode, or additional redox mediator mentioned above) are discussed below.
[0140] Zn / Zn that can be mentioned in this article 2+ Examples of redox mediators include, but are not limited to, Zn / Zn(OH)4 2- 、H6ZnW 12 O 40 and zinc porphyrin dyes.
[0141] Ferrocene derivatives that may be mentioned herein include ferrocene derivatives having the following structure:
[0142]
[0143] In the above formula, X is selected from H, F, Cl, Br, I, NO2, COOR, C 1-20 Alkyl, CF3 and COR, where R is H or C 1-20 Alkyl; n is 0 to 20.
[0144] Specific derivatives of ferrocene that may be mentioned herein include, but are not limited to, ferrocene bromide, ferrocenylmethyl dimethylethyl ammonium bis(trifluoromethanesulfonyl)imide (Fc1N112-TFSI), N-(pyridin-2-ylmethylene)-1-(2-(diphenylphosphino)ferrocenyl)ethylamine (FeCp2PPh2RCN), 1,1-dimethylferrocene (DMFc), tetraferrocene, di(sodium ethylsulfonate)ferrocene (C 14 H 16 FeS2O6Na2) and bis(tris(methysulfonate)ferrocene(C 16 H 22 FeS2O6Na2).
[0145] In a specific embodiment of the present invention that may be mentioned herein, the ferrocene derivative may be bis(tris(methysulfonate)ferrocene (C 16 H 22 FeS2O6Na2) or sodium bis(ethylsulfonate)ferrocene (C 14 H 16 FeS2O6Na2).
[0146] Viologens are 1,1'-disubstituted 4,4'-bipyridinium ions (in which the nitrogen atom of the pyridine ring is replaced by an alkyl group (e.g. C1 to C 12 alkyl) substituted), with a suitable counterion (e.g., Cl - 、F - Br - and I - ). An example of this type of viologen is paraquat. When used herein, viologen may include related compounds such as diquat and dipolaron.
[0147] Other redox mediators that can be used in the present invention are described below with reference to WO2013 / 012391, which is incorporated herein by reference. The redox mediators mentioned in said document can be used in the presently disclosed battery system, and these mediators are discussed below.
[0148] Metallocene derivatives used as redox mediators may have the following structure:
[0149]
[0150] In the above formula, M can be Fe, Co, Ni, Cr or V; each cyclopentadienyl ring can be independently substituted by one or more of the following groups: F, Cl, Br, I, NO2, COOR, C 1-20 Alkyl, CF3 and COR, where R can be H or C 1-20 alkyl.
[0151] The triarylamine derivatives used as redox mediators may have the following structure:
[0152]
[0153] In the above formula, each benzene ring can be independently substituted by one or more of the following groups: F, Cl, Br, I, NO2, COOR, C 1-20 Alkyl, CF3 and COR, where R can be H or C 1-20 alkyl.
[0154] Phenothiazine derivatives and phenoxazine derivatives used as redox mediators may have the following structure:
[0155]
[0156] R a Can be H or C 1-20 The alkyl group, X may be O or S, and the aromatic moieties are each optionally substituted by one or more of the following groups: F, Cl, Br, I, NO2, COOR, R, CF3, and COR, wherein R may be H or C 1-20 alkyl.
[0157] The carbazole derivative used as a redox mediator may have one of the following structures:
[0158]
[0159] R x Can be H or C 1-20 The alkyl group and the aromatic part are each optionally substituted by one or more of the following groups: F, Cl, Br, I, NO2, COOR, C 1-20 Alkyl, CF3 and COR, where R can be H or C 1-20 alkyl.
[0160] Transition metal complexes used as redox mediators can have one of the following structures:
[0161]
[0162] In the above formula, M can be Co, Ni, Fe, Mn, Ru or Os; each aromatic moiety is unsubstituted or substituted by one or more of the following groups: F, Cl, Br, I, NO2, COOR', R', CF3, COR', OR' or NR'R", R' and R" can each independently be H or C 1-20 alkyl; X, Y and Z can each independently be F, Cl, Br, I, NO2, CN, NCSe, NCS or NCO; and Q and W can each independently be selected from the following:
[0163]
[0164] In these formulas, R1, R2, R3, R4, R5 and R6 can each be F, Cl, Br, I, NO2, COOR', R', CF3, COR', OR' or NR'R". Likewise, each aromatic moiety is optionally substituted with one or more of the following groups: F, Cl, Br, I, NO2, COOR', C 1-20 alkyl, CF3, COR', OR' or NR'R", wherein R' and R" can each independently be H or C 1-20 For the avoidance of doubt, the points of attachment of each of Q and W to the metal are through the two nitrogen atoms present in each of the above-mentioned Q and W molecules, and thus Q and W act as bidentate ligands in the transition metal complex.
[0165] Specific transition metal complexes that may be mentioned herein include, but are not limited to, ferrophenanthroline ferrous ion, iron (II / III) tris(2,2'-bipyridine), iron (II / III) tris(2,2'-methylbipyridine) and iron (II / III) tris(2,2'-methoxybipyridine).
[0166] Aromatic derivatives used as redox mediators may have the following structures:
[0167]
[0168] In these formulas, R1, R2, R3, R4, R5 and R6 can each be C 1-20 alkyl, F, Cl, Br, I, NO2, COOR', CF3, COR', OR', OP(OR')(OR") or NR'R", wherein R' and R" can each independently be H, C 1-20 alkyl.
[0169] The nitroxide radical used as a redox mediator may have the following structure:
[0170]
[0171] In these formulas, R1 and R2 can each independently be C 1-20 R1, R2 and N may be taken together to form a heteroaryl, heteroarylalkyl or heterocycloalkyl ring.
[0172] Disulfides used as redox mediators may have the following structures:
[0173] R1—SS—R2.
[0174] In these formulas, R1 and R2 can each independently be C 1-20 alkyl, COOR', CF3, COR', OR' or NR'R", wherein R' and R" can each independently be H or C 1-20 alkyl.
[0175] Anodic redox mediators and, when present, cathode redox mediators and additional redox mediators may be provided in the cathode electrolyte and the anolyte at any suitable concentration. For example, in embodiments of the invention that may be mentioned herein, in the cathode electrolyte or the anolyte, the total concentration of the redox mediator present in the supporting electrolyte may be 0.05M to 8M, such as 0.05 to 2M, such as 0.1M to 1.5M, such as 0.15M to 1.0M, such as 0.25M to 0.5M.
[0176] Typically, the concentration of the cathodic redox mediator in the catholyte is at least 0.3 M, such as at least 0.5 M, such as at least 1 M. Typically, the concentration of the anodic redox mediator in the anolyte is from 0.001 M to 1 M, optionally from 0.01 M to 0.05 M, more optionally from 0.015 M to 0.035 M, such as from 0.02 M to 0.03 M.
[0177] As mentioned above, the supporting electrolyte contains one or more ion-providing compounds or salts. Any suitable material may be used in this capacity.
[0178] Thus, in some embodiments of the invention as mentioned herein, the catholyte and the anolyte may each comprise an inorganic base. In alternative embodiments as mentioned herein, the catholyte and the anolyte may each comprise a neutral metal salt.
[0179] Non-limiting examples of suitable ions that can be provided by a supporting electrolyte (e.g., by an inorganic base and / or a neutral metal salt) include, but are not limited to, carboxylic acids and salts formed from complementary ions. Suitable ions that may be mentioned herein include, but are not limited to, ammonium ions, lithium ions, sodium ions, potassium ions, magnesium ions, aluminum ions, copper ions, chloride ions, bromide ions, nitrate ions, and hydroxide ions (e.g., ammonium ions, lithium ions, sodium ions, potassium ions, chloride ions, and hydroxide ions, optionally wherein the supporting electrolyte is formed from one or more of the group consisting of sodium ions, potassium ions, hydroxide ions, and chloride ions).
[0180] In examples of such embodiments, the catholyte and the anolyte can each contain an inorganic base, and the anodic redox mediator can be a redox mediator suitable for alkaline conditions, such as DHPS, dihydroxyanthraquinone (DHAQ) or oxazine 7 / 8-carboxylic acid. Alternatively, the catholyte and the anolyte can each contain a neutral metal salt, and the anodic redox mediator can be a redox mediator suitable for neutral conditions, such as sulfonated ferrocene, viologen redox mediator or amino acid functionalized phenazine. Those skilled in the art will appreciate that other redox mediators can be used for alkaline or neutral conditions, as discussed herein.
[0181] Examples of suitable inorganic bases that may be mentioned herein include one or more of NaOH, LiOH and KOH.
[0182] Examples of suitable neutral metal salts that may be mentioned herein include one or more of the group consisting of MCl, MBr, M2SO4 and MNO3, wherein M is selected from Li, Na, K and NH4.
[0183] The catholyte may further comprise a salt of the first metal, such as an oxide of the first metal or a hydroxide of the first metal.
[0184] As mentioned herein, the first metal is selected from the group consisting of alkali metal, alkaline earth metal, III group metal and transition metal. As described above, the characteristics of the first metal are not particularly limited, as long as it can be oxidized by anodizing reduction mediators. In some embodiments of the present invention that may be mentioned herein, the first metal may be selected from the group consisting of alkali metal, alkaline earth metal, aluminum, zinc and iron. The examples of specific metals that can be used as the first metal and can be mentioned in this article include lithium, potassium, sodium, magnesium, aluminum, zinc and iron. In some specific embodiments of the present invention, the first metal can be zinc.
[0185] When the first metal is zinc, the area capacity of zinc can be 10 mAh / cm 2 Up to 450mAh / cm 2 , such as 10mAh / cm 2 Up to 300mAh / cm 2, such as 12mAh / cm 2 Up to 250mAh / cm 2 , such as 12.2mAh / cm 2 Up to 250mAh / cm 2 .
[0186] Similarly, in some embodiments, the discharge capacity of the redox flow battery can be 10 mAh / cm 2 Up to 450mAh / cm 2 , such as 10mAh / cm 2 Up to 300mAh / cm 2 , such as 12mAh / cm 2 Up to 250mAh / cm 2 , such as 12.2mAh / cm 2 Up to 250mAh / cm 2 .
[0187] In some embodiments of the present invention, the current density of the redox flow battery can be 10 mA / cm 2 Up to 300mA / cm 2 , such as 10mA / cm 2 Up to 200mA / cm 2 , such as 10mA / cm 2 Up to 100mA / cm 2 , such as 20mA / cm 2 Up to 80mA / cm 2 .
[0188] As discussed herein, the use of an anodic redox mediator advantageously avoids / reverses the generation of "dead metal" in redox flow batteries. Thus, in some embodiments of the invention as may be mentioned herein, the capacity fade rate of the redox flow battery may be less than 0.02% / day for at least 1500 hours.
[0189] In a specific embodiment of the invention that may be mentioned herein, the redox flow battery may be an alkaline redox flow battery comprising the following features:
[0190] The anodic redox mediator comprises DHPS (e.g., 20 mM DHPS);
[0191] The catholyte optionally comprises [Fe(CN)6] 3- and [Fe(CN6)] 4- One or two of the following (e.g. 0.6M [Fe(CN)6] 3- and 0.05M[Fe(CN6)] 4- );
[0192] The first metal comprises Zn;
[0193] the catholyte and anolyte each comprising an inorganic base (e.g., NaOH) (e.g., 3.8 M NaOH); and
[0194] The catholyte comprises zinc oxide or zinc hydroxide (eg 0.3 M ZnO).
[0195] In a specific embodiment of the invention that may be mentioned herein, the redox flow battery may be an alkaline redox flow battery comprising the following features:
[0196] The anodic redox mediator comprises DHPS (e.g., 20 mM DHPS);
[0197] The catholyte contains [Fe(CN)6] 3- and [Fe(CN6)] 4- One or two of the following (e.g. 0.6M [Fe(CN)6] 3- and 0.05M[Fe(CN6)] 4- );
[0198] The first metal comprises Zn;
[0199] the catholyte and anolyte each comprise an inorganic base (e.g., NaOH) (e.g., the catholyte and anolyte each comprise 3.8 M NaOH or the anolyte comprises 3.8 M NaOH and the catholyte comprises 1.8 M NaOH); and
[0200] The catholyte optionally comprises zinc oxide or zinc hydroxide (eg, 0.3 M ZnO).
[0201] In a specific embodiment of the invention that may be mentioned herein, the redox flow battery may be a neutral redox flow battery comprising the following features:
[0202] The anodic redox mediator comprises sulfonated ferrocene (e.g., 5 mM ferrocene sulfonate, sodium salt);
[0203] The catholyte optionally comprises I - and I2Br - One or both of the following:
[0204] The first metal comprises Zn;
[0205] The catholyte and anolyte each comprise a neutral metal salt (e.g., NaCl, such as 1 M NaCl); and
[0206] The catholyte comprises a neutral zinc salt (eg, ZnCl2, such as 0.1 M ZnCl2).
[0207] In a specific embodiment of the invention that may be mentioned herein, the redox flow battery may be a neutral redox flow battery comprising the following features:
[0208] The anodic redox mediator comprises sulfonated ferrocene (e.g., 20 mM ferrocene sulfonate, sodium salt);
[0209] The catholyte optionally comprises I - and I2Br - One or both of the following:
[0210] The first metal comprises Zn;
[0211] The catholyte and anolyte each comprise a neutral metal salt (e.g., 4 M total NaCl, KBr, and / or KCl); and
[0212] The catholyte comprises a neutral zinc salt (eg, 1 M total ZnCl2, ZnBr2, or ZnI2).
[0213] In any of the embodiments discussed above, the catholyte and anolyte can be aqueous.
[0214] The present invention also provides an electrolyte suitable for use in a redox flow battery, comprising:
[0215] Solvent (e.g. water);
[0216] Neutral or basic metal salts; and
[0217] One or more redox mediators selected from the group consisting of DHPS and sulfonated ferrocene.
[0218] In the electrolyte according to the present invention, the neutral or alkaline metal salt may be as described above. For example, the metal salt may contain zinc oxide or zinc hydroxide. The redox mediator may be DHPS.
[0219] The electrolyte according to the present invention may further comprise an inorganic base, such as a metal hydroxide. Suitable examples of metal hydroxides are alkali metal hydroxides (eg NaOH, KOH or LiOH).
[0220] The present invention also provides a kit comprising an anolyte and a catholyte as described herein. For example, the present invention provides a kit comprising:
[0221] (i) a catholyte comprising:
[0222] an oxide of a first metal or a hydroxide of a first metal, and
[0223] Neutral or basic metal salts; and
[0224] (ii) an anolyte comprising:
[0225] a redox mediator having a redox potential relative to a standard hydrogen electrode that is more positive than the redox potential of the first metal relative to a standard hydrogen electrode, and
[0226] Neutral or basic metal salts.
[0227] In the kit according to the present invention, the first metal, the neutral or basic metal salt and the redox mediator may be as described above.
[0228] For example, in some embodiments of the kit according to the invention:
[0229] The first metal may be zinc;
[0230] The neutral or basic metal salt may be selected from NaCl and NaOH;
[0231] The redox mediator may be selected from one or more of the group consisting of DHPS and sulfonated ferrocene.
[0232] Provided that when the metal salt is NaCl, the redox mediator is sulfonated ferrocene, and when the metal salt is NaOH, the redox mediator is DHPS.
[0233] All features disclosed in this specification may be combined in any combination. Each feature disclosed in this specification may be replaced by an alternative feature for the same, equivalent or similar purpose. Therefore, unless otherwise expressly stated, each feature disclosed is only an example of a series of equivalent or similar features.
[0234] The ability of the redox flow battery of the present invention to avoid the "dead metal" problem is described with respect to zinc redox flow batteries. By way of example, redox-mediated zinc chemistry can be used to solve the "dead zinc" problem in alkaline systems. Figure 1 As shown, during the discharge process, when the "active zinc" (on the electrode) is depleted, the redox mediator (RM) dissolved in the electrolyte and having a higher potential than zinc will further chemically oxidize the "dead zinc". - It shuttles back to the electrode where it is electrochemically regenerated. Subsequently, electrons are transferred from the “dead zinc” to the oxidized RM to form Zn[(OH)4] 2- , and under neutral conditions form Zn 2+. During the cycling process, the lost capacity of the "dead zinc" can be continuously restored by the redox-mediated zinc oxidation process, achieving high stability of the battery. Using this redox-mediated closed-loop chemical-electrochemical cycle, the "dead zinc" electrically separated from the electrode will be indirectly and continuously regenerated. Therefore, the inactive zinc will be immediately eliminated during each discharge process without accumulation, and the harmful effects will be mitigated. In the following, the redox mediator DHPS / DHPS-2H (alkaline) or Fc-SO3Na / Fc + This cycle is experimentally demonstrated in the example of -SO3Na (neutral). This proves that the present invention can be applied to both alkaline and neutral battery systems.
[0235] From the above description, those skilled in the art can easily determine the essential features of the present invention, and without departing from its spirit and scope, various changes and modifications can be made to the present invention to adapt it to various uses and conditions. Therefore, other embodiments are also within the claims.
[0236] Hereinafter, embodiments of the present invention are described in more detail with reference to the following examples. However, the present disclosure is not limited thereto. In addition, contents not described in the present disclosure can be fully understood by those skilled in the art and will not be shown herein.
[0237] Example
[0238] Material
[0239] All chemicals were purchased from Sigma-Aldrich and used without further purification. DHPS was synthesized using the same method as in the literature (Zhang, F. et al., J. Am. Chem. Soc. 2021, 143, 223-231). Nafion 115 (Dupont) membrane was purchased from Chemours. Carbon felt was purchased from Liaoyang Jingu Carbide Co., Ltd or SGL Carbon and used as is.
[0240] Example 1. Assembly and testing of zinc-based flow batteries
[0241] In zinc-based symmetric flow batteries, zinc metal pressed onto carbon felt serves as both cathode and anode.
[0242] In an alkaline zinc-iron flow battery, carbon felt is used as the cathode; zinc metal sheets pressed onto the carbon felt are used as the anode. Nafion 115 membrane is used to separate the catholyte and anolyte. Fluororubber gaskets and PTFE tubing (Cole-Parmer) are used to construct the cell. The active area is 13.5 cm 2, and the membrane was soaked in 3.8 M NaOH overnight before use. 2 ) was used as a zinc-based symmetric flow battery, with 20 mL and 60 mL of 3.8 M NaOH and 0.3 M ZnO / 3.8 M NaOH with / without 20 mM DHPS as the anolyte and catholyte, respectively. 1.65 g zinc was used for the cathode, and 0.20 g zinc was used for the anode. The current density was 20 mA / cm 2 For high area capacity (92.0 mAh / cm 2 ) was used as a zinc-based symmetric flow battery, with 60 mL and 120 mL of 3.8 M NaOH and 0.3 M ZnO / 3.8 M NaOH with 20 mM DHPS used as the anolyte and catholyte, respectively. 4.15 g of zinc was used for the cathode, and 1.50 g of zinc was used for the anode. The current density was 50 mA / cm 2 For an area capacity of 152 mAh / cm 2 For the zinc-iron flow battery, 110 mL and 300 mL of 3.8 M NaOH and 0.6 M Fe(CN)6 3- / 0.05M Fe(CN)6 4- / 1.8M NaOH was used as the anolyte and catholyte, respectively. 2.50 g of zinc was used for the anode, and the current density was 50 mA / cm 2 For an area capacity of 250 mAh / cm 2 For the zinc-iron flow battery, 150 mL and 400 mL of 3.8 M NaOH with 30 mM DHPS and 0.6 M Fe(CN)6 3- / 0.05M Fe(CN)6 4- / 1.8M NaOH was used as the anolyte and catholyte, respectively. 4.06g zinc was used for the anode, and the current density was 80mA / cm 2 For galvanostatic measurements, the battery was charged to its theoretical capacity and discharged to the cut-off voltage. The tests were performed using an Arbin battery tester.
[0243] In a neutral zinc-iodine flow battery, carbon felt is used as the cathode; zinc metal sheets pressed onto the carbon felt are used as the anode. Nafion 115 membrane is used to separate the catholyte and anolyte. Fluororubber gaskets and PTFE tubing (Cole-Parmer) are used to construct the cell. The active area is 13.5 cm 2, and the membrane was soaked in 1M ZnCl2 or 2M KCl solution overnight before use. For the zinc-based symmetric flow battery, 20mL 20mM Fc-SO3Na / 1M ZnCl2 was used as the anolyte, and 80mL 1M ZnCl2 was used as the catholyte. 0.2g zinc was used for the anode, and 1.5g zinc was used for the cathode. The current density was 20mA / cm 2 For the zinc-iodine flow battery, 30 mL of 1 M ZnI2 + 2 M KBr + 2 M KCl was used as the cathode electrolyte, and 20 mL of 1 M ZnI2 + 2 M KBr + 2 M KCl + 20 mM Fc-SO3Na was used as the anode electrolyte, with a current density of 20 mA / cm 2 .
[0244] Example 2. Electrochemical measurements
[0245] Cyclic voltammetry (CV) measurements were performed using an Autolab electrochemical workstation (Metrohm, PGSTAT30) using a three-electrode configuration consisting of a glassy carbon working electrode, a platinum counter electrode, and a Hg / HgO reference electrode. The glassy carbon working electrode was polished for 2 min using 0.3 and 0.05 μm alumina slurries and then sonicated in deionized water before each test. In order to determine the overpotential of different cell components, a 4-electrode electrochemical characterization was performed in which 60 mL of 0.6 M Fe(CN)6 3- / 0.05M Fe(CN)6 4- / 1.8M NaOH and 20mL of 3.8M NaOH with / without 7mM DHPS + 0.1g zinc plate on carbon felt or 30mL of 3.8M NaOH with 20mM DHPS were used as catholyte and anolyte, respectively. Two Hg / HgO reference electrodes were inserted into both the positive and negative electrode compartments with an active area of 5cm 2 And the current density is 30mA / cm 2 .
[0246] Example 3. Characterization
[0247] In situ UV-Vis spectra of DHPS-mediated zinc oxidation reactions were collected using a SHIMADZU UV-1800 spectrometer. The setup included a reaction tank, DHPS electrolyte, pump, piping system, detector, monochromator, and light source. A custom-designed spectroelectrochemical cell with a 0.6 mm optical path length was connected to the outlet of the reaction tank. The DHPS absorbance changes during the reaction process were recorded. For chemical reaction tests, the supporting electrolyte was 3.8 M NaOH, and for kinetic tests, the supporting electrolyte was 0.4 M Zn(OH)4 2- / 3M NaOH.
[0248] The dynamic in situ FTIR measurements were performed using a PerkinElmer Frontier MIR / FIR system in attenuated total reflectance (ATR) mode to detect the structural evolution of DHPS during different stages. The setup included a catholyte, an anolyte containing zinc, a pump, a flow field, electrodes, a membrane, an IR source, and a detector. DHPS flowed through an ATR crystal and collected 1600 to 1000 cm -1 FTIR spectrum with a resolution of 4 cm -1 .
[0249] XRD measurements were performed with a powder XRD diffractometer system (Bruker D8 Advance), and SEM measurements were performed with a Zeiss Supra40.
[0250] Example 4. DHPS-mediated zinc chemistry
[0251] The half-wave potential (E) of DHPS and Zn was measured by CV. 1 / 2 ). DHPS / DHPS-2H and [Zn(OH)4] 2- E of Zn 1 / 2 Respectively -0.90V and -1.30V (relative to standard hydrogen electrode (SHE)). Therefore, the driving force of the zinc oxidation reaction mediated by DHPS can be as large as 0.40V. The reaction between DHPS and zinc was first monitored by in-situ UV-Vis spectroscopy through a spectroelectrochemical flow cell. The UV-Vis spectrum of the DHPS solution shows a main absorption at about 435nm, which weakens after adding excess zinc. At the same time, another absorption peak generated at 354nm due to the formation of DHPS-2H appears and becomes stronger with the reaction. The concentration changes of DHPS and DHPS-2H were calculated based on the standard calibration curve. After zinc was added to the DHPS solution, the absorbance of DHPS-2H at 470nm rose almost instantly and reached a steady state in a short time, indicating that the reaction was rapid, which will be further discussed later. The concentration of DHPS-2H was stable at 1.1 mM, while the concentration of DHPS decreased from 1.4 mM to 0.3 mM, indicating that the chemical reaction between zinc and DHPS can be triggered even when a small amount of DHPS is included in the electrolyte.
[0252] To elucidate the mechanism of the DHPS-mediated zinc oxidation reaction, ATR-FTIR spectra were measured at different stages of the reaction, using which the bonding information of DHPS can be detected in real time. The C=N bond at 1550 cm-1 was clearly observed during the standing process. -1The stretching vibration at 1272 cm gradually disappears after adding zinc to the electrolyte (Sun, T. et al., Nano Res. 2020, 13, 676-683). -1 A new peak attributed to CN bond formation appeared at , indicating the reduction of DHPS (Li, L. et al., J. Mater. Chem. A 2020, 8, 26013-26022). Interestingly, during the subsequent discharge process, the C=N vibration did not reappear, and the CN group of the reduced DHPS still existed, indicating that the DHPS-mediated zinc oxidation process reached a stable state. The following describes the two-step closed-loop DHPS-mediated zinc oxidation chemistry. During the discharge process, DHPS-2H is electrochemically oxidized by losing electrons to the electrode:
[0253] DHPS-2H+2OH - -2e - →DHPS+2H2O (1)
[0254] The oxidized DHPS is then reduced by nearby zinc as observed by UV-Vis measurements:
[0255]
[0256] As indicated by ATR-FTIR measurements, the system reaches a steady state when the flux of DHPS formed on the electrode is balanced with the flux of DHPS consumed by zinc oxidation outside the electrode.
[0257] Example 5. Kinetic studies
[0258] The reaction rate between DHPS and zinc is determined by different parameters, such as [Zn(OH)4] 2- The concentration of DHPS, the energy barrier of mass transfer and interfacial charge transfer, etc. Therefore, the kinetic study was first carried out by monitoring the OCP change of DHPS in the presence of excess zinc powder (Zhang, H. et al., Adv. Mater. 2021, 33, 2006234). The entire reaction process was protected by N2 gas, a rotating disk electrode (RDE) was used as the working electrode (WE), and a Hg / HgO electrode was used as the reference electrode (RE). OCP changes with time, and the slope b can be calculated:
[0259]
[0260] where E is the equilibrium potential of DHPS, which is determined by the Nernst equation:
[0261]
[0262] Here, is the formal potential, so the slope can be written as:
[0263]
[0264] Here, is the initial concentration of DHPS. Considering that the evolution of OCP is determined only by the chemical reaction, the normalized effective current is defined to describe the flux of the reaction (Zhou, M. et al., Chem 2017, 3, 1036-1049; and Zhou, M. et al., Adv. Energy Mater. 2019, 9, 1901188):
[0265]
[0266] In addition, we can get The relationship between and b:
[0267]
[0268] Here, R is the universal gas constant, T is the absolute temperature (298K), F is the Faraday constant, V is the electrolyte volume, 0 is 1M. For the same overpotential The conditions, among which is a constant that causes b and Therefore, a larger slope (b) will correspond to a faster reaction rate. As [Zn(OH)4] 2- As the concentration of Zn increased or the concentration of DHPS decreased, the slope of OCP relative to time decreased, indicating that the reaction rate between DHPS and zinc weakened.
[0269] Considering the solubility of [Zn(OH)4] in the electrolyte 2- The presence of Zn(OH)4 may affect the OCP measurement of DHPS / DHPS-2H, so the concentration of DHPS was determined by in situ UV-Vis spectroscopy. 2- There is a large potential difference between Zn and Zn, so it is expected The Tafel behavior between and η allows the exchange current i0 to be determined:
[0270]
[0271] Here, α is the transfer coefficient. The flux of the reaction increases with the increase of overpotential. When η>0.32V, becomes saturated, indicating a mass transfer limited process. At lower overpotentials, the interfacial charge transfer process becomes the rate determining step and exhibits With respect to the linear variation of η, a clear deviation is observed (see the dashed line with α set to 1 for the unidirectional charge transfer process). Considering that at low η, the concentration of DHPS drops to a relatively low level, this deviation can be rationalized by the presence of trace oxygen, which rapidly oxidizes DHPS-2H and attenuates the drop in DHPS concentration, and thus the effective reaction flux is inferred by extrapolating the dashed line to the intercept of log(i0) About 2.7×10 -5 A.
[0272] Note that the i0 of DHPS / DHPS-2H on the glassy carbon electrode is about 3.3×10 -5 A, which is comparable to the redox-targeted reaction rate on zinc.
[0273] In addition to comparable CV peak currents, the peak-to-peak separation (ΔE) between the anodic and cathodic peak potentials of zinc was ∼0.17 V ( Figure 2 ), indicating that DHPS has a positive effect on [Zn(OH)4] 2- / Zn had no significant effect on the reaction.
[0274] Molecules with redox potentials more positive than zinc (>-1.26 V relative to SHE under alkaline conditions and >-0.76 V relative to SHE under neutral conditions) can be used for zinc oxidation. DHPS / DHPS-2H and Fc-SO3Na / Fc were measured by CV in 3.8 M NaOH and 1 M NaCl, respectively. + -SO3Na redox potential. Figure 2 As shown in Figure 2, the redox potential of the DHPS / DHPS-2H pair is -0.90 V (vs. SHE), which is lower than that of Zn / Zn[(OH)4] 2- The redox potential of the pair is higher and can be used as a RM under alkaline conditions. + -SO3Na has a redox potential of 0.30 V (vs. SHE), which is lower than Zn / Zn 2+ The redox potential of is corrected so that it can be used as the RM for neutral conditions ( Figure 3 ).
[0275] In addition, four-electrode measurements were performed using two Hg / HgO reference electrodes (RE) in both the positive and negative electrode compartments to monitor the Zn / [Fe(CN)6] 3- / 4-The local voltage drop between different battery components of the flow battery (Gao, M. et al., Mater. Today Energy 2020, 18, 100540; and Weng, G.-M. et al., Energy Environ. Sci. 2017, 10, 735-741). At 30 mA / cm 2 The voltage drop ΔV between the positive electrode and RE1 was monitored during the charge and discharge process at a current density of + , the voltage drop between the negative electrode and RE2 is ΔV - , the voltage drop ΔV between RE1 and RE2 across the membrane m and the voltage drop ΔV between the positive and negative electrodes c The difference ΔV between the charge and discharge processes of the anolyte with and without DHPS - 42 mV and 47 mV, respectively, indicating that the presence of DHPS has no adverse effect on the zinc reaction kinetics. In addition, the difference ΔV between the charge and discharge of the flow battery in the presence of DHPS was further analyzed. c , ΔV m and ΔV + , and calculated to be 793mV, 350mV, and 41mV respectively. Obviously, the total battery voltage ΔV c The value is significantly larger than ΔV m , ΔV + and ΔV - The sum of , indicating that in addition to the series resistance of the membrane, the voltage loss also comes from the series resistance of the flow battery (~306mV). In the absence of zinc, from DHPS / [Fe(CN)6] 3- / 4- Similar results were obtained for the 4-electrode flow battery. Figure 4 middle.
[0276] Example 6. Zinc-based symmetric flow battery
[0277] A zinc-based symmetric flow cell (as described in Example 1) was assembled to study the role and performance of DHPS. Figure 5 a shows the condition at 20 mA / cm 2 The current density and 100% DOD (charged to the theoretical capacity of zinc and fully discharged to the cut-off voltage) of the Zn2+ cell were 12.2 mAh / cm2 and 100% DOD (charged to the theoretical capacity of zinc and fully discharged to the cut-off voltage) respectively. 2 ) under the conditions of 1.5 mAh / cm2 and 1.5 mAh / cm3, respectively. For the cell without DHPS in the anolyte, the utilization of zinc was about 79% (9.6 mAh / cm2) in the first 62 cycles. 2), and then gradually decreases to nearly 0, with a capacity decay rate of about 0.27 mAh / cm per cycle. 2 In stark contrast, in the presence of 20 mM DHPS in the anolyte, zinc utilization improved to 94% (11.5 mAh / cm 2 ), and there was no significant capacity decay in the first 120 cycles. Its capacity began to decline from the 125th cycle, and recovered instantly with the replacement of the counter electrode, indicating that the capacity decay originated from the depletion of active zinc on the counter electrode ( Figure 6 ). The representative voltage distribution of the battery is Figure 5 b. During the discharge process, the long high voltage plateau corresponds to the stripping of active zinc on the electrode, and is followed by a short low voltage plateau of oxidation of DHPS-2H and associated DHPS-mediated oxidation of “dead zinc”. This is confirmed by the capacity of the second plateau exceeding the theoretical capacity of DHPS (2.2 mAh / cm 2 Relative to 1.6 mAh / cm 2 ). In addition, in the presence of DHPS in the anolyte, the surface of the carbon felt electrode after cycling was as clean as that of the original carbon felt (see Figure 7 In contrast, in the absence of DHPS, some zinc and ZnO deposition sites were observed on the carbon felt ( Figure 8 ).
[0278] To further evaluate the ability of DHPS to regenerate “dead zinc”, the 2 At a current density of 100% and 100% DOD, a high zinc areal capacity (92.0 mAh / cm 2 ) and a zinc-based symmetric flow battery with 20 mM DHPS in the anolyte. Figure 5 As shown in c, the battery exhibits ~90.8 mAh / cm 2 The discharge capacity of DHPS is 98.9% and the Coulombic efficiency (CE) is 98.9%. Considering that the battery is charged to the theoretical capacity of zinc and fully discharged, the CE also roughly corresponds to the utilization of zinc in each cycle, because the discharge capacity of DHPS is negligible ( Figure 5 d). Cumulative discharge capacity was used to evaluate the cycling stability of DHPS-mediated zinc symmetric flow battery ( Fig. 9 )(Chen, Y. et al., Joule 2019, 3, 2255-2267), which was determined to be 7.08 Ah / cm after 78 cycles. 2 (Theoretically 7.11Ah / cm 2 ), corresponding to a significantly low capacity fade rate of 0.005% / cycle. Importantly, the polarization of the voltage profile did not deteriorate during the entire cycling process ( Figure 5d), and the morphology of the carbon felt after the cycle is almost as clean as the original carbon felt ( Figure 10-11 These results confirm the ultrastable cycling performance of the DHPS-mediated Zn oxidation process under operating conditions, showing promising prospects for Zn-based full battery applications.
[0279] In addition to alkaline conditions, the zinc-based symmetric flow battery was also tested under neutral conditions with 20 mM Fc-SO3Na as RM. Fig.12 As shown, at 20mA / cm 2 At a current density of 1.5 Å, the zinc-based symmetric flow battery can achieve 100 stable cycles with almost no capacity decay, and the CE can reach a high value of 98.9%.
[0280] In the present disclosure, with the help of RM dissolved in the electrolyte, the cycling stability of zinc electrodes at high DOD and areal capacity is significantly enhanced. As an example, DHPS is used as the RM for alkaline zinc-based flow batteries, while anionic sulfonated ferrocene derivatives (Fc-SO3Na) are used as RM for neutral zinc-based flow batteries. The "dead" zinc formed is effectively regenerated in each cycle.
[0281] Fig.13 Redox molecules that may be useful with zinc are summarized in .
[0282] Example 7. Alkaline zinc-iron flow battery (AZIFB)
[0283] Because of the promising results of the symmetric cell, we further investigated the Zn / [Fe(CN)6] 3- / 4- DHPS-mediated “dead zinc” regeneration process in a full cell of a deep-cycle flow battery. 2 The zinc area capacity was tested at a current density of 152 mAh / cm 2 The cycling performance of AZIFB ( Fig.14 a). AZIFB with 30 mM DHPS in the anolyte showed stable cycling performance over 1500 h. The cell was charged to the theoretical capacity (calculated by the amount of zinc used in the anode). Therefore, the zinc was almost 100% active during the entire cycling process.
[0284] In order to evaluate the capacity decay rate more accurately, the cumulative discharge capacity versus time was plotted to analyze the durability of AZIFB, as shown in Fig.14b. With 30 mM DHPS in the anolyte, AZIFB exhibited ultra-stable cycling performance over 1,500 h with an average CE of 97.5%. Because the battery was charged to the theoretical capacity of the zinc loaded in the battery, this indicates that the utilization of zinc was almost 1 during the entire cycling process. The capacity decay rate (97.5% × theoretical capacity of zinc × number of cycles, Fig.14 b) (Chen, Y. et al., Joule 2019, 3, 2255-2267), which was determined to be 36.7 Ah / cm after 247 cycles. 2 (From the 2nd cycle to the 248th cycle). Considering the theoretical cumulative value of 37.1Ah / cm 2 The capacity decay rate was calculated to be 0.0048% / cycle or 0.019% / day (based on the discharge capacity of the second cycle), corresponding to a capacity retention rate of 93.3% after 1 year of continuous operation. This represents the best reported cycling performance for deep-cycle zinc-based flow batteries. AZIFBs without DHPS in the anolyte were also tested. Fig.15 ). Even at 92.0mAh / cm 2 The lower area capacity and 20mA / cm 2 At a current density of 3.3 mAh / cm per cycle, the battery also showed 2 Rapid capacity decay.
[0285] Fig.14 c shows the voltage distribution of AZIFB at the 10th, 150th, and 200th cycles. The long plateaus in the discharge and charge curves are related to the Zn oxidation and [Zn(OH)4] 2- Reduction process, and the short platform corresponds to the oxidation or reduction of DHPS-2H and DHPS. Because the capacity of DHPS is significantly less than that of Zn, the potential mismatch between DHPS and Zn has only a slight effect on the total energy efficiency (EE). As revealed by previous 4-electrode measurements and kinetic studies, the relatively low EE of AZIFB is mainly attributed to the large series resistance of the battery, and it is expected that by optimizing the battery design and membrane compared with those reported, there is ample room for improvement (Hu, J. et al., Adv. Funct. Mater. 2021, 31, 2102167; Hu, J. et al., Angew. Chem. Int. Ed. 2020, 59, 6715-6719; and Wu, J. et al., J. Am. Chem. Soc. 2021, 143, 13135-13144). In addition, in the 10th cycle, the discharge capacity of DHPS-2H is about 4.40 mAh / cm higher than the charge capacity of DHPS. 2, indicating that DHPS recovers a similar amount of “dead zinc”. This value becomes slightly higher at the 150th and 200th cycles, indicating that although DHPS is effectively regenerating at each cycle, more inactive zinc is formed with cycling. In addition, it appears that the capacity of DHPS is lost with cycling, while the total discharge capacity remains almost unchanged (note that the shortened low-voltage charging plateaus at the 150th and 200th cycles are partly due to smaller sampling points during the long measurements to reduce file size). In addition, the carbon felt remains intact after this long cycling process ( Figure 16-Figure 17 ). These results together demonstrate the effectiveness of DHPS-mediated Zn chemistry in battery cycling performance.
[0286] To further understand the effect of DHPS on Zn deposition during the charging process, we characterized the morphology of Zn deposited on the anodic carbon felt (under 50 mA / cm 2 152mAh / cm 2 ). According to the SEM images, the presence of DHPS does not seem to have a significant effect on Zn deposition, and its morphology is similar to those reported in the literature (Wang, RY, Kirk, DW & Zhang, GX, J. Electrochem. Soc. 2006, 153, C357). Fig.18 The top view of the carbon felt electrode shows that the deposited Zn changes from micron-sized "boulder-like" particles with clear crystal facets surrounding individual carbon fibers to submicron "moss-like" porous deposits filling between the fibers. Fig.19 In the cross-sectional view, porous Zn deposits dominate inside the carbon felt.
[0287] In addition to the cycle stability of the Zn electrode, area capacity is another key design parameter of AZIFB. For a given total electrode area (or power), a higher Zn area capacity leads to a higher energy, which is particularly suitable for long-duration discharge applications. Similarly, for a given energy requirement, if the energy requirement is met, a higher Zn area capacity will only require a smaller electrode area (or the number of cells in the stack), which reduces the cost (see Example 8 below). In order to evaluate the DHPS-mediated Zn chemistry at high area capacity, the Zn chemistry was tested at 80 mA / cm 2 The Zn loading was 200 mAh / cm2 at 100% DOD. 2 and 250mAh / cm 2 AZIFB( Figure 20-21). At such high current density and DOD, good cycling stability with average CE of 97.4% and 96.4% was achieved, revealing the excellent robustness of the DHPS-mediated Zn oxidation reaction for practical applications. Although the above cycling stability tests for Zn are rigorous, for alkaline Zn-based flow batteries, [Zn(OH)4] 2- The limited solubility of ZnO at high pH, which usually requires a low volume capacity of the anolyte, should be addressed for high-density energy storage. Fig. 22 As shown, the solubility of ZnO in 3.8 M NaOH is about 0.5 M, which translates to a volumetric capacity of only 26.8 Ah / L.
[0288] In this study, DHPS was used as the RM due to its suitable redox potential, high chemical stability, and fast reaction rate under alkaline conditions. Using the DHPS-mediated strategy, AZIFBs using Zn as the anode and ferrocyanide as the catholyte active material have demonstrated high electrochemical performance up to 250 mAh / cm 2 The significantly enhanced cycling stability at a Zn utilization close to 1 is achieved with a high Zn areal capacity of 152 mAh / cm 2 The battery can be operated at 100% DOD and 50 mA / cm 2 The battery was operated for more than 1,500 h at a current density of 1.3 Å, with a capacity decay rate of 0.019% / day, which is the best ever reported. We anticipate that this redox-mediated strategy will have broad applicability in other electrolyte systems involving solid / liquid phase transition reactions and provide a credible approach to ultimately address the “dead zinc” problem for ultra-robust and deep-cycling zinc-based redox flow batteries.
[0289] Example 8. Analysis of AZIFBs with different zinc areal capacities
[0290] Condition 1: For a fixed power (P) requirement, the active area (A) of a single electrode is 0.89 m 2 , the current density (j) is 50mA / cm 2 , and the single cell voltage (U0) is 1.5V.
[0291] Here, we take 10kW as an example:
[0292] P=U×I=n×U0×j×A=n×1.5×0.05×8900=10000
[0293] The calculated number of cells (n) is 15.
[0294] Energy (E) can be calculated based on:
[0295] E=Q×U=n×Q 面积 ×A×n×U0=15 2 ×1.5×8900×Q 面积
[0296] Here, Q 面积 is the area capacity of a single cell.
[0297] For a 20 mAh / cm 2 Low Q 面积 The battery is calculated to have an E of about 60 kWh, which allows for continuous operation for 6 hours.
[0298] For a 200mAh / cm 2 of high Q 面积 The battery is calculated to have an E of about 600kWh, which allows for about 60h of continuous operation.
[0299] As a result, high area capacity is advantageous for long duration operating conditions when meeting power requirements.
[0300] Condition 2: For a fixed energy requirement and to meet the basic power requirement, the single electrode active area (A) is 0.89 m 2 , the current density (j) is 50mA / cm 2 , and the single cell voltage (U0) is 1.5V.
[0301] Here, we take 600kWh as an example:
[0302] Energy (E) can be calculated based on:
[0303] E=Q×U=n×Q 面积 ×A×n×U0=n 2 ×1.5×8900×Q 面积 =600000
[0304] For a 200mAh / cm 2 of high Q 面积 The number of cells (n) is calculated to be about 15.
[0305] For a 20 mAh / cm 2 Low Q 面积 For a battery of this type, n is calculated to be approximately 47.
[0306] As a result, to achieve the same energy, when the area capacity is increased from 200 mAh / cm 2 Reduced to 20 mAh / cm 2When the number of cells is increased from 15 to 47, the number of cells will increase. Therefore, under this condition, the larger area capacity can reduce the number of cells in the stack, thereby reducing the cost (Moore, MA et al., A Comparison of the Capital Costs of a Vanadium Redox-Flow Battery and a Regenerative Hydrogen-Vanadium Fuel Cell, 2015).
[0307] In summary, DHPS-mediated zinc chemistry was investigated for the first time in alkaline Zn-based flow batteries to regenerate the capacity of “dead zinc”. The presence of low concentrations of DHPS in the anolyte led to a significant improvement in the cycling performance of the zinc electrode in terms of areal capacity and deep cycling conditions, by virtue of a fast redox-targeted reaction with inactive zinc. Based on this strategy, the Zn electrode was recharged at 50 mA / cm 2 and 152 mAh / cm at 100% DOD. 2 The ultra-stable AZIFB with high Zn loading exhibited an ultra-low capacity decay rate of 0.019% / day over more than 1,500 hours. In addition, the capacity of the Zn-containing AZIFB was significantly increased at 250 mAh / cm during long-term cycling. 2 Even higher area capacity and 80mA / cm 2 At a current density of 1.3 Å, AZIFB achieved a high Zn utilization of 96.5%. Through rigorous testing, the method demonstrated in this work provides a reliable solution for long-life and deep-cycle applications of alkaline Zn-based flow batteries at high material loading and current density. In addition, the redox-mediated approach is expected to provide an effective way to universally solve the capacity loss problem of other metal-based batteries with different electrolyte conditions.
[0308] As described above, the present invention provides an effective solution to the "dead metal" problem, as exemplified in the context of "dead zinc" in zinc redox flow batteries.
Claims
1. A redox flow battery comprising: a catholyte chamber comprising a catholyte and a cathode; an anolyte chamber comprising an anolyte and an anode comprising a first metal; and an ion selective membrane disposed between the cathode chamber and the anode chamber, in: The first metal is selected from the group consisting of alkali metals, alkaline earth metals, Group III metals, and transition metals; The anolyte comprises an anodic redox mediator; and The anodic redox mediator has a redox potential relative to a standard hydrogen electrode that is more positive than a redox potential of the first metal relative to a standard hydrogen electrode.
2. The redox flow battery according to claim 1, wherein the anode redox mediator is selected from the group consisting of phenazine redox mediators, quinone redox mediators, viologen redox mediators, ferrocene derivatives, nitrogen oxide radical redox mediators, and alloxazine redox mediators. Optionally, the anodic redox mediator is selected from one or more of the group consisting of DHPS, amino acid functionalized phenazine, dihydroxyanthraquinone or its derivatives, sulfonated ferrocene and alloxazine 7 / 8-carboxylic acid, More optionally, the anodic redox mediator is one or more selected from the group consisting of DHPS and sulfonated ferrocene.
3. The redox flow battery of claim 1, wherein the catholyte further comprises a cathode redox mediator.
4. The redox flow battery of claim 3, wherein the cathode redox mediator comprises one or more of the following pairs: [Fe(CN)6] 3- / [Fe(CN6)] 4- ; O2 / OH - ; MnO4 - / MnO4 2- ; I3 - / I - ; Br2 / Br - ; (I - 、Br - / I3 - 、I2Br - ); Fe 3+ / Fe 2+ ; (2,2,6,6-tetramethylpiperidin-1-yl)oxy (TEMPO) derivatives; and MnO2 / Mn 2+ 。 5. A redox flow battery according to claim 3 or claim 4, wherein the concentration of the cathodic redox mediator in the catholyte is at least 0.3M, such as at least 0.5M, such as at least 1M.
6. A redox flow battery according to any one of the preceding claims, wherein the catholyte comprises a salt of the first metal, Optionally, the salt of the first metal is an oxide of the first metal or a hydroxide of the first metal.
7. A redox flow battery according to any one of the preceding claims, wherein the concentration of the anodic redox mediator in the anolyte is from 0.001 M to 1 M, Optionally, 0.01M to 0.05M, More optionally, 0.015M to 0.035M, Such as 0.02M to 0.03M.
8. A redox flow battery according to any one of the preceding claims, wherein: (a) the catholyte and the anolyte each comprise an inorganic base; or (b) The catholyte and the anolyte each contain a neutral metal salt.
9. The redox flow battery according to claim 8 or 9, wherein: (a) the catholyte and the anolyte each contain an inorganic base, and the anodic redox mediator is DHPS; or (b) The catholyte and the anolyte each contain a neutral metal salt, and the anodic redox mediator is sulfonated ferrocene.
10. The redox flow battery according to claim 8 or 9, wherein: (a) the inorganic base is selected from one or more of NaOH, LiOH and KOH; (b) The neutral metal salt is selected from at least one of the group consisting of MCl, MBr, M2SO4, and MNO3, wherein M is selected from Li, Na, K, and NH4.
11. The redox flow battery of any one of the preceding claims, wherein the first metal is selected from the group consisting of alkali metals, alkaline earth metals, aluminum, zinc, and iron; Optionally, wherein the first metal is selected from the group consisting of lithium, potassium, sodium, magnesium, aluminum, zinc and iron.
12. A redox flow battery according to any one of the preceding claims, wherein the first metal is Zn.
13. The redox flow battery according to claim 12, wherein the area capacity of zinc in the redox flow battery is 10 mAh / cm 2 Up to 450mAh / cm 2 , such as 10mAh / cm 2 Up to 300mAh / cm 2 , such as 12mAh / cm 2 Up to 250mAh / cm 2 , such as 12.2mAh / cm 2 Up to 250mAh / cm 2 .
14. A redox flow battery according to any one of the preceding claims, wherein the anode comprises carbon and the first metal, Optionally, wherein the anode comprises carbon fibers and the first metal.
15. The redox flow battery according to any one of the preceding claims, wherein the current density of the redox flow battery is 10 mA / cm 2 Up to 300mA / cm 2 , such as 10mA / cm 2 Up to 200mA / cm 2 , such as 10mA / cm 2 Up to 100mA / cm 2 , such as 20mA / cm 2 Up to 80mA / cm 2 .
16. The redox flow battery according to any one of the preceding claims, wherein the discharge capacity of the redox flow battery is 10 mAh / cm 2 Up to 450mAh / cm 2 , such as 10mAh / cm 2 Up to 300mAh / cm 2 , such as 12mAh / cm 2 Up to 250mAh / cm 2 , such as 12.2mAh / cm 2 Up to 250mAh / cm 2 .
17. The redox flow battery of any preceding claim, wherein the capacity fade rate of the redox flow battery is less than 0.02% / day over at least 1500 hours.
18. A redox flow battery according to any one of the preceding claims, wherein the catholyte and the anolyte are aqueous.
19. A redox flow battery according to any one of the preceding claims, wherein: The anodic redox mediator comprises DHPS; The cathode electrolyte contains [Fe(CN)6] 3- and [Fe(CN6)] 4- One or both of the following: The first metal comprises Zn; The catholyte and the anolyte each comprise an inorganic base (e.g., NaOH); and The catholyte comprises zinc oxide or zinc hydroxide.
20. The redox flow battery according to any one of claims 1 to 18, wherein: The anodic redox mediator comprises sulfonated ferrocene; The cathode electrolyte comprises I - and I2Br - One or both of the following: The first metal comprises Zn; The catholyte and the anolyte each comprise a neutral metal salt (e.g., NaCl, KBr and / or KCl); and The catholyte comprises a neutral zinc salt (eg, ZnCl2, ZnBr2, and / or ZnI2).
21. The redox flow battery of claim 19 or 20, wherein the catholyte and the anolyte are aqueous.
22. An electrolyte suitable for use in a redox flow battery, comprising: Solvent (e.g. water); Neutral or basic metal salts; and One or more redox mediators selected from the group consisting of DHPS and sulfonated ferrocene.
23. The electrolyte according to claim 22, wherein: The metal salt comprises zinc oxide or zinc hydroxide; and The redox mediator is DHPS.
24. The electrolyte according to claim 22 or 23, further comprising an inorganic base, Optionally, wherein the inorganic base comprises NaOH.
25. A kit comprising: (i) a catholyte comprising: an oxide of a first metal or a hydroxide of a first metal, and Neutral or basic metal salts; and (ii) an anolyte comprising: a redox mediator having a redox potential relative to a standard hydrogen electrode that is more positive than the redox potential of the first metal relative to a standard hydrogen electrode, and The neutral or basic metal salt.
26. The kit of claim 25, wherein: The first metal is zinc; The neutral or alkaline metal salt is selected from NaCl and NaOH; The redox mediator is selected from one or more of the group consisting of DHPS and sulfonated ferrocene, Provided that when the metal salt is NaCl, the redox mediator is sulfonated ferrocene, and when the metal salt is NaOH, the redox mediator is DHPS.
Citation Information
Patent Citations
A redox flow battery system
WO2013012391A1